2017
DOI: 10.1017/s0954422417000208
|View full text |Cite
|
Sign up to set email alerts
|

Milk products in the dietary management of childhood undernutrition – a historical review

Abstract: The present narrative review outlines the use of milk products in infant and young child feeding from early history until today and illustrates how research findings and technical innovations contributed to the evolution of milk-based strategies to combat undernutrition in children below the age of 5 years. From the onset of social welfare initiatives, dairy products were provided by maternal and child health services to improve nutrition. During the last century, a number of aetiological theories on oedematou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 197 publications
(237 reference statements)
0
6
0
1
Order By: Relevance
“…In contrast, the effects of milk protein were seen in the tool's fine motor and language domains, which also reflect cognitive functions such as problem-solving, reasoning, and executive functions. Milk products have been used in food supplementation since early programme initiatives [36] and have been studied for their benefits for growth and health, especially in children with poor nutritional status [37]. However, very few studies have assessed the effects of milk on cognitive outcomes.…”
Section: Plos Medicinementioning
confidence: 99%
“…In contrast, the effects of milk protein were seen in the tool's fine motor and language domains, which also reflect cognitive functions such as problem-solving, reasoning, and executive functions. Milk products have been used in food supplementation since early programme initiatives [36] and have been studied for their benefits for growth and health, especially in children with poor nutritional status [37]. However, very few studies have assessed the effects of milk on cognitive outcomes.…”
Section: Plos Medicinementioning
confidence: 99%
“…In this study, families provided with locally-made RUSF demonstrated significantly greater levels of compliance, suggesting that there is greater cultural support for locally-made nutritional supplements. Considering the logistical and financial burden upon health systems to procure imported RUTF, we expect that locally-made RUSF may be used safely in providing nutritional intervention to malnourished children in LMICs [ 28 ]. The chemical composition of the nutritional interventions is summarized in Table 6 .…”
Section: Discussionmentioning
confidence: 99%
“…While the Indian rice diet has a percentage digestibility of 77%, when milk too is consumed the digestibility increases to 87% (WHO, 2002). There is still no scientific evidence about the minimum amount of milk protein required to exert an adequate effect on weight gain and growth among children of different age groups, while the impact of other sources of protein and other beneficial compounds needs to be considered (Sherbaum and Srour, 2018).…”
Section: Animal Based Foods To Improve Protein Qualitymentioning
confidence: 99%